Mewujudkan Desa Ramah Plastik: Replikasi Program Shodakoh Sampah di Padukuhan Blimbingsari, Caturtunggal, Yogyakarta. - Mutrofin Mutrofin (Islamic Management and Empowerment Journal, 2020)
This research aims to increase knowledge and skills in managing the environment, especially plastic waste through systematic and sustainable manner. The research was conducting in Code River community. This research using a Community Based Research (CBR) approach method. By this method researcher is involved in a program that is formulated and applied by the community to solve environmental problems caused by household waste. This research is one of the results of community development practicum conducted by students of Islamic Community Development Study Program UIN Sunan Kalijaga Yogyakarta. The program carried out in this study uses a garbage shodakoh system where the waste goes through the stages of sorting, recycling and selling. In addition, this system is strengthened with Islamic values in the practice of shodakoh for handling existing waste. The results of this study indicate that there is an increase in community knowledge and skills in optimizing household waste, especially plastics, into various recycling. With this program there are a variety of positive impacts generated in the form of increased community cash income, increasing harmony and increasing public awareness not to throw garbage or waste in the river.